Nonlinear Speed Controller Supported by Direct Torque Control Algorithm and Space Vector Modulation for Induction Motors in Electrical Vehicles - Aliskan, I.; Gulez, K.; Tuna, G.; Mumcu, T. V.; Altun, Y. (KAUNAS UNIV TECHNOLOGY, 2013)
Energy mode functions and their inverse signal dynamics can be used for the design of controllers in classical control algorithms, which use the error signals of related system parameters in general mode. Different from this common approach, Lyapunov function-based controller design is preferred and motor mechanical speed parameter is incorporated into the control operation in this study. The results of the experimental studies conducted for this study prove that when both electrical and mechanical parameters of the system are taken into consideration, the proposed controller, nonlinear speed controller supported by direct torque controller and space vector modulation, performs better than classical controllers and can be realized successfully.
Keywords: Nonlinear speed controller; induction motor; direct torque control; space vector modulation; MACHINES; Engineering